DEVELOPMENT OF AN -BASED DIGITAL COMIC "TARI SAMAN" FOR HUMAN MOVEMENT SYSTEM MATERIAL - Irdalisa, Irdalisa; Hanum, Erlia; Zulherman, Zulherman; Nurhayati, Elis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Scientific literacy skills are still low, and students' lack of interest in getting to know culture is a current educational issue, so innovative, creative and interesting learning media are needed to increase interest in reading and the formation of national cultural character in students. The development of digital comics in the field of science has been carried out by many researchers, but there are still few who combine the material with local wisdom to form cultural characters. This ethnoscience- based digital comic designed to be a pilot project and learning resource for teachers and students in Indonesia in mastering science, technology, skills and attitudes based on the Independent Learning Curriculum. The data was analyzed by processing validator response data with a Likert scale which was converted into qualitative data . The research subjects were media, material and language experts, 60 high school students in class XI high school science, and 6 biology teachers. The instruments used were expert validation tests and questionnaires. The data was analyzed by processing validator response data with a Likert scale which was converted into qualitative data. The purpose of this research can measure the effectiveness of the ethnoscience -based digital comic "Tari Saman" on movement system material to improve students' scientific literacy skills and national cultural character according to P5 (Strengthening Pancasila Student Profile Project). This research uses the 4D method (Define, Design, Develop, Disseminate). The validity test results show that ethnoscience-based digital comics “tari saman” have a moderate level of validity with an Aiken index value > 0.4.  the results of  the feasibility test were 88% by the teachers and 90% by students and media practicability were 88% by teachers and 89% by students. It can be concluded that ethnoscience-based digital comics “tari saman” are valid, feasible and practical to use as supporting media for Biology learning.